Wicked prey - Sandford, John, 1944 Feb. 23-; Ferrone, Richard (New York, N.Y. : Penguin Audio, 2009)
In the nineteenth installment of the Prey series, Minnesota investigator Lucas Davenport struggles to protect his daughter Letty from a vengeful psychopathic pimp who blames Davenport for his handicap. All the while, a professional thief plans to rob the city of Minneapolis blind right before the Republican National Convention. Can Davenport protect his daughter and ensure the security of Minneapolis?
Unabridged.
Compact discs.
Read by Richard Ferrone.
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Private investigators -- Minnesota -- Minneapolis -- Fiction; Minneapolis (Minn.) -- Fiction; Mystery fiction; Audiobooks